Molecular Mechanism of LEDGF/p75 Dimerization - Lux, Vanda; Brouns, Tine; Čermáková, Kateřina; Srb, Pavel; Fábry, Milan; Mádlíková, Marcela; Hořejší, Magdalena; Kukačka, Zdeněk; Novák, Petr; Kugler, Michael; Brynda, Jiří; DeRijck, Jan; et al. (Structure (London, England, 2020)
Dimerization of many eukaryotic transcription regulatory factors is critical for their function. Regulatory role of an epigenetic reader lens epithelium-derived growth factor/p75 (LEDGF/p75) requires at least two copies of this protein to overcome the nucleosome-induced barrier to transcription elongation. Moreover, various LEDGF/p75 binding partners are enriched for dimeric features, further underscoring the functional regulatory role of LEDGF/p75 dimerization. Here, we dissected the minimal dimerization region in the C-terminal part of LEDGF/p75 and, using paramagnetic NMR spectroscopy, identified the key molecular contacts that helped to refine the solution structure of the dimer. The LEDGF/p75 dimeric assembly is stabilized by domain swapping within the integrase binding domain and additional electrostatic "stapling" of the negatively charged α helix formed in the intrinsically disordered C-terminal region. We validated the dimerization mechanism using structure-inspired dimerization defective LEDGF/p75 variants and chemical crosslinking coupled to mass spectrometry. We also show how dimerization might affect the LEDGF/p75 interactome.
Keywords: paramagnetic NMR; protein-protein interaction; epigenetics; Protein Multimerization; domain swapping; Humans; transcription; mezibuněčné signální peptidy a proteiny; lidé; proteinové domény; Protein Domains; Static Electricity; Intercellular Signaling Peptides and Proteins; PSIP1; eletrostatic stapling; mixed-lineage leukemia; multimerizace proteinu; statická elektřina